Some Results on Pachpatte-Type of Opial Inequality - Yisa Oluwatoyin Anthonio; Abimbola Abolarinwa; Kamilu Rauf (Pan-American Journal of Mathematics)
This paper applies the modified Jensen inequality to generalize some cases of Pachpatte results of Opial-type inequalities on time scales. These inequalities further generalize some existing results.